Teratogeneous Effects of Gynuraprocumbens (Lour.) Merr. Ethanol Extract Against Musculus Fetal - Rahimatul Uthia; Ira Oktaviani RZ; Riza Anggraini; Fitra Fauziah (JURNAL PROTEKSI KESEHATAN, 2020)
AbstractThis study looked at the teratogenous effects of ethanol extracts ofGynuraprocumbens (Lour.) Merr. on the white mice fetus. Experimental animalsconsisted of 24 mices, 4 male mices and 20 female mices, divided into 4groups, namely the negative control group, ethanol extracts ofGynuraprocumbens (Lour.) Merr. 150 mg/kgBW; 300 mg/kgBW; and 600mg/kgBW. Provision is made from the 6th day until the 15th day ofpregnancy. Laparactomy is carried out on the 18th day of pregnancy. Theparameters observed were body weight of mices, number of fetuses,average fetal weight, and macroscopic observation of the fetus. The resultsshowed that the parent's body weight, number of fetuses, and average fetalweight were significantly different (sig <0.05). Macroscopic observation ofthe fetus obtained slow growth in ethanolic extracts dose of 600 mg/kgBW.This study can be concluded that the ethanol extract ofGynuraprocumbens(Lour.) Merr.has a teratogeniceffect on the fetus of whitemice.